2020
DOI: 10.1080/08897077.2019.1573777
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Academic Detailing on Benzodiazepine use among Veterans with Posttraumatic Stress Disorder

Abstract: Background: Benzodiazepine use in the US Veterans Administration (VA) has been decreasing; however, a small number of veterans with posttraumatic stress disorder (PTSD) continue to receive benzodiazepine. Academic detailing, a targeted-educational outreach intervention, was implemented at VA to help reduce the disparity between existing and evidence-based practices, including the reduction in benzodiazepine use in veterans with PTSD. Since evidence to support the national implementation of academic detailing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In addition to the specific survey-defined strategies that were actively used during implementation, we found that pre-implementation academic detailing was one of the strongest predictors of case review completion. Academic detailing is, in and of itself, an evidence-based, multi-component implementation strategy that includes needs assessments, education, and focused training and has contributed to successful implementation efforts across a number of domains [24,[28][29][30][31]. In VA, academic detailing is typically conducted by clinical pharmacists, who deliver face-to-face, 1-on-1 training.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the specific survey-defined strategies that were actively used during implementation, we found that pre-implementation academic detailing was one of the strongest predictors of case review completion. Academic detailing is, in and of itself, an evidence-based, multi-component implementation strategy that includes needs assessments, education, and focused training and has contributed to successful implementation efforts across a number of domains [24,[28][29][30][31]. In VA, academic detailing is typically conducted by clinical pharmacists, who deliver face-to-face, 1-on-1 training.…”
Section: Discussionmentioning
confidence: 99%
“…BZD-focused AD programs have been associated with reductions in BZD, although demonstrated among prescribers who care for the veteran population. 24 In terms of policy initiatives at the health system level, delivery of focused education on evidence-based guidelines for BZD prescribing, risks of BZD use, and alternative pain management options may be important components to integrate into opioid-focused AD programs to help address inappropriate prescribing of BZD. Additionally, incorporation of clear, actionable guidance into opioid-focused AD programs on how to use the data found in state PMPs may help to facilitate informed clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Academic detailing is, in and of itself, an evidence-based, multi-component implementation strategy that includes needs assessments, education, and focused training and has contributed to successful implementation efforts across a number of domains. 24,[28][29][30][31] In VA, academic detailing is typically conducted by clinical pharmacists, who deliver face-to-face, 1-on-1 training. Our ndings support the notion that academic detailing is effective as a preimplementation, or "preparation" strategy, as we found that academic detailing measured prior to implementation was associated with the outcome.…”
Section: Discussionmentioning
confidence: 99%